Arquitetura na rota das cachoeiras: casas de terra na paisagem cultural do Distrito de Taquaruçu, Estado do Tocantins - Pereira, Marielle Rodrigues (Universidade de Lisboa, 2021)
The hypothesis of this thesis is the possibility to attribute value to vernacular architecture not only on its materiality, but above all, to incorporate its immaterial dimension, translated by the constructive traditions, whose values - material and immaterial, are inseparable and that guarantee the maintenance of the singularity Such hypothesis arose from research conducted in Taquaruçu, District of the Municipality of Palmas, located in the State of Tocantins. This place made it possible to discover the possibility of incorporating other values into vernacular architecture. The permanence of vernacular constructive traditions today, anchored by ecological and human attributes, gives a sense of existence to the landscape and constitutes the character of the place. In this sense, the study sought to provide answers about the existence of immaterial values in vernacular architecture from the arguments that base the evolution of the concept of landscape, as well as the identification of territories that elucidate constructive traditions and that constitute the universe of traditional communities. Therefore, we opted for qualitative research in Taquaruçu, based on the physical and phenomenological aspects associated with the study of natural and historical components, in order to provide answers to the elements that constitute constructive architectural territoriality - material / immaterial, natural / cultural, based on ecological, vernacular and human principles. Through the study of these three elements of the landscape, guidelines are proposed that contribute to a diagnosis of attribution of material and immaterial value associated with vernacular architecture and cultural holders of the landscape. This thesis does not intend to diminish the scope of material value traditionally incorporated into architecture, on the contrary, to point out a third option of attributing value to vernacular architecture, where both values - material and immaterial, constitute the fundamental basis of the existence of certain places.